ENT 530 Social Media Portfolio: Keknisscarves / Nurul Syazwani Mohd Jik - Mohd Jik, Nurul Syazwani (2021)
Keknisscarves which owned by Nur Anis Nafisah Binti Zahari and this is the new brand that selling the hijabs for women. This type of business is a sole proprietorship. This business is started to operate in March 2020. Since, Keknisscarves is a new brand and started her business in early 2020, so this business consist only one agent, which is Nurul Syazwani Binti Mohd Jik. The function of this agent is to perform the duties such as, marketing, handle the order and also packaging for this product as well. When I see Keknisscarves is finding for its agent, then I decided to join as I am really interested to start selling the product even as an agent. Personally, before Keknisscarves is open for an agent, I already purchase its product and I realized that her product or brand provide the high quality of hijab at the affordable prices. The material that use for this product is at the best quality which is, it is easy to shape and when the person is wearing this brand, she will not feel like hot and the colours of this hijab is very beautiful. Next, I decided to become an agent as I can see that not everyone in real life, such as students that did not have so much money to buy the branded hijab. All of the collection of Kekniscarves such as Ombra Shawl and Eyelash Cotton Shawl did not reach RM 20. So that, I think the price is affordable for everyone to buy and wear. It is suitable for everyone to wear regardless of their ages as this kind of shawl did not only focus for the teenagers and youngsters but also can be wear by our mom as well. So that, my customers have their own choice whether to buy it for themselves or as a gift to other people. Lastly, I have uploaded the collection of Ombra Shawl and Eyelash Cotton Shawl on my Facebook page. I also have posted the teasers, hard sell and soft sell on my Facebook page. I also use the technique of AIDCA in doing my copywriting.